Classification and functional analyses of putative virulence factors of Mycobacterium tuberculosis: A combined sequence and structure based study. (August 2020) - Shahbaaz, Mohd; Potemkin, Vladimir; Bisetty, Krishna; Hassan, Md. Imtaiyaz; Hussien, Mostafa A.
Graphical abstract: Highlights: Functional annotation of 1000 hypothetical proteins using Bioinformatics' techniques. Categorization of annotated HPs into enzymes, transport, and other cellular activities. Classification of putative virulence factors. Structure-based functional analyses of the classified virulent HPs. Molecular Dynamic (MD) simulation-based assessment of the predicted structure stability. Abstract: The emergence of the drug-resistant mechanisms in Mycobacterium tuberculosis poses the biggest challenges to the current therapeutic measures, which necessitates the identification of new drug targets. The Hypothetical Proteins (HPs), a class of functionally uncharacterized proteins, may provide a new class of undiscovered therapeutic targets. The genome of M. tuberculosis contains 1000 HPs with their sequences were analyzed using a variety of bioinformatics tools and the functional annotations were performed. The functions of 662 HPs were successfully predicted and further classified 483 HPs as enzymes, 141 HPs were predicted to be involved in the diverse cellular mechanisms and 38 HPs may function as transporters and carriers proteins. Furthermore, 28 HPs were predicted to be virulent in nature. Amongst them, the HP P95201, HP P9WM79, HP I6WZ30, HP I6 × 9T8, HP P9WKP3, and HP P9WK89 showed the highest virulence scores. Therefore, these proteins were subjected to extensive structure analyses and dynamics of their conformations were investigated using the principles of molecular dynamics simulations, each for a 150 ns time scale. This study provides a deeper understanding of the undiscovered drug targets and the generated outputs will facilitate the process of drug design and discovery against the infection of M. tuberculosis .